Tinjauan Artificial Intelligence untuk Smart Government - Saluky Saluky (ITEJ (Information Technology Engineering Journals), 2018)
Higher population growth and urbanization to seek a better life keep the city's population increasing and if not controlled it is estimated that by 2030 it will reach 70% of the urban population. The higher the population then the service to the community must be further enhanced because the city's problems will be more complex. The ability of government to adapt to all changes requires artificial intelligence in order to process the data obtained, understand and provide effective and efficient actions in order to serve all its citizens. The result of this survey study is to present artificial intelligence techniques such as search, reasoning, planning, and learning. Artificial intelligence method that is widely used is an artificial neural network to solve the problem.